Assessment of "danger to self and others": a study of the Mental Health Review Tribunal's interpretation of "dangerousness" - Hepworth, David Robert (1982)
The general research aim was to examine the process by which the mental health review tribunal decided on the 'dangerousness' of the person before them as a basis for their judgement about release or continued detention.